Teachers' Experiences with Networked Classrooms in Norway. (4th July 2017) - Helleve, Ingrid; Almås, Aslaug Grov
Abstract : The aim of this study, based on response on a questionnaire from 65 teachers in upper secondary schools, is to gain insight into how teachers experience and practice their role as leaders in the digital classroom. Research shows that teachers seldom are asked about their opinions concerning use of technical device. From 2007 all Norwegian students in upper secondary schools were given a computer from the authorities. Politicians argued for pedagogical use of ICT, for example, through interactive device like social networking sites. However, recent national reports show that teachers mainly use ICT for administrative and not for pedagogical purposes. Findings from the current study show that teachers adjust the technology to their existing pedagogy and continue their existing practice. To a small extent the technology's interactive abilities are utilized. Technological device is powerful. Possible consequences of placing technology on every student's desk are discussed. The teachers' future concern is to control Internet and to have possibilities to develop and discuss pedagogical use of technology in classrooms with their colleagues.